Economic analysis of Ghana's chicken industry - Nti, Frank Kyekyeku (Kansas State University, 2018)
Increasing feed price and the adverse effect of low cost poultry imports have put economic pressure on domestic poultry production in Ghana. With an increasing population and per capita income, poultry demand is expected to grow at a higher rate. There is, therefore, a need to improve domestic farm performance and/or competitiveness. This study estimates an input-oriented distance function to evaluate the technical efficiencies and cost efficiencies of chicken production in Ghana in a non-parametric framework using a dataset that includes all known chicken farms in Ghana. The choice of feed, that constitutes about 74% and 91% of the total variable cost in broiler and layer operations, respectively, may have direct effects on the financial position and performance of farms. As a result, the study also identifies determinants of producers’ feed demand decision to inform policies to manage the availability, affordability and accessibility of feed. In identifying these determinants, the double hurdle model popular in the literature for modelling zero dependent variables is used to examine the decision mechanism underlying Ghanaian poultry farmers’ feed demand decisions. The results indicate that layer production is a more efficient enterprise than broiler production. However, noticeable differences in the production behavior and efficiency level among different farm classes, and among farms located in different geographic regions exist. In general, medium-sized farms combine their inputs and resources more optimally than large- and small-sized farms. The variables identified to influence efficiency levels differ substantially across the types of chicken enterprises and among estimated efficiency indicators. While the geographic location of farms, farm size, feed type, source of commercial feed and own feed preparation methods significantly influenced many of the performance indicators, farmers’ educational level had little effect on producers’ optimal inputs combination. The decision on the type and quantity of feed used is critical to enhancing producers’ profit margins. The study found that the decision to use own feed or commercial feed were largely influenced by similar factors but with opposite effects. For instance, the study finds that among other factors, the experience of farm operator, having a crop farm, farm location in a rural area, and farm size drive the decision to produce own feed but reduces the likelihood of purchasing commercial feed. On the other hand, age of farm operator and many regional dummies motivate the use of commercial feed but demotivates the using self-prepared feed. Differences also exist in the factors that influence the quantity of own feed produced and the quantity of commercial feed purchased among the three types of chicken enterprises.
Keywords: Agricultural economics